FAKTOR - FAKTOR YANG MEMPENGARUHI PARTISIPASI MASYARAKAT TERHADAP PEMBANGUNAN WISATA MANGROVE DI DESA PENGUDANG KABUPATEN BINTAN - Silvani, Tantri; Haidawati; Fitria Ulfah (Department of Socio-economic Fisheries, Marine Science and Fisheries Faculty, Raja Ali Haji Maritime University, 2024)
Pengudang Village is a tourist village located in Bintan Regency. The main tourist attraction in Pengudang Village is mangrove tourism. Mangrove tourism has its own charm for tourists, especially foreign tourists. Mangroves in Pengudang Village are very beautiful and their habitats are maintained, this cannot be separated from the participation of the community because their management is community-based. The importance of community participation in supporting the development of mangrove tourism, because effective development requires involvement (participation) from various parties (stakeholders), especially the community. Therefore, researchers are interested in researching